A comparative study of vaginal misoprostol, dinoprostone gel, foley catheter, extra amniotic saline infusion along with vaginal misoprostol for induction of labor at term - Shetty, Ektha M.; Neravi, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Objective of this study was to study the effect of vaginal misoprostol, dinoprostone gel, foley catheter, extra amniotic saline infusion along with vaginal misoprostol for induction of labor at term on maternal and fetal outcome. Methods: A one-year prospective observational study was conducted in the department of obstetrics and gynecology, SDM College of Medical Science and Hospital, Dharwad. Totally 100 postdated primigravida women with singleton gestation, vertex presentation and intact membrane who were induced with any four methods of induction 1) Tab. misoprostol 25 µg vaginally, 2) Intracervical dinoprostone gel, 3) Foley catheter and 4) Extra amniotic saline infusion along with tab. misoprostol 25 µg vaginally with 25 patients selected in each group, by random allocation technique and included in the study. Outcome measures analysed were the demographic profile, bishop score, induction to delivery interval, mode of delivery, maternal and fetal complications. Statistical analysis was done using SPSS 17 software. Results: Mean induction delivery interval was significant between PGE1 versus foley group (p=0.0034). In this study, 60% patients in dinoprostone group had Vaginal delivery and 72% in the EASI + misoprostol group underwent cesarean section (p=0.0372). NICU admission was maximum with EASI + vaginal misoprostol group and minimum with vaginal misoprostol alone. Conclusions: The groups were comparable with respect to maternal age, bishop score and fetal weight. The vaginal misoprostol group had shortest induction delivery interval. The maximum number of patients in dinoprostone gel group underwent vaginal delivery with a highest cesarean section and NICU admission with the EASI + misoprostol group.